THE EFFECT OF PREOPERATIVE ALPRAZOLAM IN THE REDUCTION OF ANXIETY IN PATIENTS UNDERGOING CARDIAC SURGERY (Journal of Medical & Health Sciences Review, 2025)
Background: Anxiety before cardiac surgery is likely to be accompanied by physiological changes that may influence surgical results. Alprazolam as pharmacological therapy could help stabilize these indicators improving the patients’ comfort and respectively perioperative conditions. This research will seek to prove if alprazolam decreases preoperative anxiety without adverse effects to promote better perioperative care practice using a controlled trial design. The effects of preoperative anxiety are observed in 30–80% of patients having major surgery, notably, cardiac procedures. Physiological changes caused by the anxiety can interfere with the anesthetic management and recovery due to increase in heart rate and blood pressure. Although anxiolytic drugs such as alprazolam are widely available, we know little about their effects on patients undergoing cardiac surgery. The purposes of this study were to fill this gap by determining the effectiveness and safety of ES in reducing preoperative anxiety of cardiac patients.Objective: To assess the influence of preoperative alprazolam on preoperative anxiety levels in heart surgery patients.Methodology: Randomized controlled study was performed in Hameed Latif Hospital, Lahore. The patients were 200 undergoing elective coronary artery bypass graft (CABG) or valve replacement surgery. The 14 randomly assigned participants were assigned to either the alprazolam group at some oral dosage of 0.5 mg or to the placebo group. Change the structure of the following sentence Physiological parameters were measured before and after drug administration, preoperatively and postoperatively. SPSS 26 was used for statistical analysis and significance set to p < 0.05.Results: Statistical analysis showed no statistically significant differences between the two groups in baseline physiological markers. When anxiety markers are analyzed after drug delivery, the alprazolam group was reduced in respiration rate (p = 0.04) before surgery. Nevertheless, other metrics including heart rate, blood pressure, and oxygen saturation did not show statistically significant variations.Conclusion: Preoperative alprazolam treatment did improve physiological markers of anxiety, notably respiratory rate, in the heart surgery patients in a mildly attenuated fashion. However, although it might help in lowering preoperative anxiety, its effect on the rest of physiological outcomes was negligible. However further dose and also other pharmaceutical treatments for anxiety management in cardiac surgery patients need to be identified.